How Does Prenatal Exercise Affect Labor and Delivery? A Review of the Influence of Prenatal Physical Activity on the Course of Vaginal Birth - Łuczak, Klaudia; Dudek, Patryk; Ulicka, Wiktoria; Pięta, Justyna; Chudzikowski, Marcel; Tabeau, Adrianna; Pawlik, Agnieszka; Sitarek, Hanna; Prus, Joanna; Prokopiuk, Agata (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Regular physical activity during pregnancy is associated with many maternal health benefits, including a reduced risk of complications during pregnancy. This review explores its impact on vaginal birth outcomes, focusing on labor induction, duration, pain tolerance, instrumental delivery rates, and episiotomy or laceration occurrences. Results: Studies suggest that prenatal exercise may lower the likelihood of labor induction and instrumental deliveries. Regular physical activity, including aerobic exercises, resistance training, and targeted prenatal workouts, has been associated with a higher rate of spontaneous labor onset, reducing the need for medical interventions such as oxytocin induction. Yoga and Pilates, in particular, have shown promising effects in enhancing pain tolerance during labor by improving flexibility, muscle strength, and relaxation techniques, which may help women manage contractions more effectively. While some research indicates that yoga can potentially shorten labor duration, findings remain inconclusive. Additionally, despite the numerous benefits of prenatal exercise, studies consistently report no significant impact on the rate of episiotomies or perineal lacerations. Conclusions: This review of literature shows that regular physical activity during pregnancy may reduce the need for labor induction, improve pain management, and lower the likelihood of instrumental deliveries. There is no doubt that prenatal physical activity may positively influence the course of spontaneous vaginal delivery by reducing the need for obstetric interventions.